The hero checks her oscilloscope. - Applewhite, A.
This paper presents a biography of Jim Ottaviani, a nuclear engineer turned technical librarian at the University of Michigan, USA, whose comic books tell true tales of scientists and engineers
Keywords: Jim Ottaviani; USA; Biography; Comic books; Nuclear engineer; Oscilloscope; Technical librarian